Pendampingan Pemasaran Industri Lokal Melalui Penggunaan Marketplace untuk Meningkatkan Hasil Produksi pada Masa Pandemi Covid-19 di Desa Sidomukti Lamongan - Fita Faridah; Zafa Wahyu Wulandari (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
The problems faced by the local industry in Sidomukti Village start from sales decline and demand turnover and conventional marketing method. The purpose of this Community Service (PKM) is to provide an understanding of the meaning and concept of the marketplace, the benefits and advantages of marketing through the marketplace, how the marketplace works, the manufacturing process, how to register and create a shop in an online store (market) and to increase production through the marketplace. The method applied was service learning which includes three stages, namely the preparation, presentation, and reflection stages. The Community Service results in providing understanding to local industry players in the Sidomukti village about marketing and selling products through the marketplace, as well as being able to create an online shop, promote their products through the marketplace and increase in sales by 10% of products from local industries being marketed in several marketplaces.